Alterations of scapular kinematics and associated muscle activation specific to symptomatic dyskinesis type after conscious control. (December 2016) - Ou, Hsiang-Ling; Huang, Tsun-Shun; Chen, Yu-Ting; Chen, Wen-Yin; Chang, Yu-Li; Lu, Tung-Wu; Chen, Ting-Han; Lin, Jiu-Jenq
Abstract: Background: Scapular orientation and movements can affect the function of the shoulder. However, evidence is limited on whether symptomatic subjects can actively maintain the scapula in a neutral position through conscious control. Objective: To investigate whether symptomatic subjects with scapular dyskinesis can achieve optimal scapular movements and associated muscle activities through conscious control. Design: A cross-sectional study. Methods: Sixty subjects with scapular dyskinesis (16 inferior angle pattern I, 16 medial border pattern II, and 28 mixed pattern) performed 3 selected exercises (arm elevation, side-lying elevation, and side-lying external rotation) with and without conscious control. Three-dimensional electromagnetic motion and electromyography were used to record the scapular kinematics and muscle activation during the exercises. Results: For scapular kinematics, significant increases in scapular external rotation (4.6 ± 3.2°, p < 0.0125) were found with conscious control during arm elevation and side-lying elevation in three groups. Significant increases in activation of the middle and lower trapezius (MT: 4.9 ± 2.4% MVIC; LT: 10.2 ± 6.8% MVIC, p < 0.0 25) were found with conscious control in 3 exercises among the 3 dyskinesis groups. Increased serratus anterior activation (SA: 11.2 ± 4.8% MVIC, p < 0.0 25) was found in the concentric phase of side-lying external rotation in the pattern I and I + II groups. Conclusion: Conscious control of the scapula can alter scapular orientation and MT, LT, and SA activation during 3 selected exercises in subjects with symptomatic dyskinesis. Specifically, conscious control during side-lying external rotation can be applied to increase SA activity in pattern I and I + II dyskinesis. Highlights: Symptomatic subjects can actively maintain the scapula by conscious control. Conscious control of the scapula can be used to improve scapular external rotation during 3 selected exercises. Conscious control of the scapula can be used to improve MT, LT, and SA performance. Conscious control during side-lying external rotation can increase SA activity in patients with scapular dyskinesis.